Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jgs.16751
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use and Deprescribing in Belgian Nursing Homes: Results from theCOME‐ONStudy

Abstract: BACKGROUND/OBJECTIVES To describe the use and deprescribing of benzodiazepine receptor agonists (BZRAs) among nursing home residents (NHRs), to evaluate appropriateness of use and to identify factors associated with BZRA use and deprescribing. DESIGN Posthoc analysis of the Collaborative Approach to Optimize Medication Use for Older People in Nursing Homes (COME‐ON) study, a cluster controlled trial that evaluated the impact of a complex intervention on potentially inappropriate prescriptions (PIPs) in nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…In a study with 2651 French NHRs receiving an antidepressant, PIP (with regard to indication, drug class, duplication and monitoring) was found in 38.4% of NHRs [ 35 ]. In a Belgian study with 418 NHRs taking a BZRA, 98% of NHRs received the BZRA for more than 4 weeks, and drug–disease and drug–drug interactions were found in two-thirds of users overall [ 36 ]. In both studies, dementia was associated with less PIP.…”
Section: Methodsmentioning
confidence: 99%
“…In a study with 2651 French NHRs receiving an antidepressant, PIP (with regard to indication, drug class, duplication and monitoring) was found in 38.4% of NHRs [ 35 ]. In a Belgian study with 418 NHRs taking a BZRA, 98% of NHRs received the BZRA for more than 4 weeks, and drug–disease and drug–drug interactions were found in two-thirds of users overall [ 36 ]. In both studies, dementia was associated with less PIP.…”
Section: Methodsmentioning
confidence: 99%
“…There is strong evidence that suggests, however, that antipsychotics have modest efficacy and are associated with cerebrovascular events and death [7][8][9]. Despite a relatively high use of benzodiazepines [10][11][12][13], evidence supporting clinical efficacy is very limited [14][15][16] and may be associated with a higher risk of falls, cognitive impairment, and sedation [17,18]. Guidelines advise against a range of antidepressants, especially those with anticholinergic effects, because of side effects and adverse effects [19].…”
Section: Introductionmentioning
confidence: 99%
“… 18 20 In the Belgian nursing home setting, a recent study by Evrard et al showed that a history of fall in the past 3 months, chronic obstructive pulmonary disease, polypharmacy, insomnia, and antidepressant use were factors associated with BZRA use. 17 On the contrary, dementia and trazodone use were factors negatively associated with BZRA use. 17 However, no study has been conducted to identify factors associated with BZRA use in older people from the general Belgian older population.…”
Section: Introductionmentioning
confidence: 98%
“… 17 On the contrary, dementia and trazodone use were factors negatively associated with BZRA use. 17 However, no study has been conducted to identify factors associated with BZRA use in older people from the general Belgian older population.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation